2015
DOI: 10.7196/sajcc.2015.v31i2.252
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition support practices in South African ICUs: Results from a nationwide pilot survey

Abstract: Background. Nutrition support of the critically ill can positively affect clinical outcomes. International audit data of nutrition practices in intensive care units (ICUs) suggest that inconsistent application of recommended nutrition support practices (NSPs) occurs. There are no data on NSPs in South African (SA) ICUs. Objective. To perform a national pilot survey of NSPs in private SA adult ICUs. Methods. A descriptive, observational, cross-sectional survey was performed among prescribers of nutrition suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…The Hill Questionnaire [5] was adapted and modified for this study. Hill's study evaluated nutrition support practices with sub-themes on nutrition screening and assessment, nutrition decision-making, enteral nutrition delivery, administration and monitoring; parenteral nutrition delivery, administration and monitoring; and the types of nutrition products used.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Hill Questionnaire [5] was adapted and modified for this study. Hill's study evaluated nutrition support practices with sub-themes on nutrition screening and assessment, nutrition decision-making, enteral nutrition delivery, administration and monitoring; parenteral nutrition delivery, administration and monitoring; and the types of nutrition products used.…”
Section: Data Collectionmentioning
confidence: 99%
“…[3] Studies have revealed that attenuation of the catabolic effects of critical illness is associated with improved outcomes in the intensive care unit (ICU). [4,5] Despite the benefits of medical nutrition therapy in the ICU, optimal nutrition approaches remain a challenge. [1,3,6] One of the challenges in achieving optimal nutrition support is variations in actual clinical nutrition practices [4,5,7] delivered to ICU patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A nation-wide pilot study that surveyed nutritional support practices in private South African (SA) adult intensive care units (ICUs) revealed disparities in reported nutrition practices, suggesting among other things, that implementation of published nutrition guidelines was not well established (Hill, 2015). That was before the establishment of the SA national enteral nutrition practice guidelines for adults, which make provision for adult patients in need of EN at all levels of public healthcare and in their households (home-based enteral nutritional therapy).…”
Section: Introductionmentioning
confidence: 99%